2020
DOI: 10.1016/j.apenergy.2019.114090
|View full text |Cite
|
Sign up to set email alerts
|

On the ease of being green: An investigation of the inconvenience of electric vehicle charging

Abstract: This paper presents a quantitative investigation of the inconvenience of electric vehicle (EV) charging relative to internal combustion engine vehicle (ICEV) fuelling in terms of the time penalty likely to be experienced by drivers. A heuristic approach to deriving idealised charging schedules from over 39,000 week-long travel diaries from the UK National Travel Survey is presented in order to quantify the expected convenience parity-the point at which EV charging and ICEV fuelling are of comparable convenienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…The study found that this was especially true for EVs with larger batteries: those with capacities above 35 kWh chose to charge on average every 3.2 days, versus every 1.5 days for those with capacities under 25 kWh [51]. To address this important point, the work presented in this paper models drivers' likely charging schedules derived from week-long travel diaries, using a heuristic method originally presented in [52], in which the focus is to minimise the number of charging events (and the associated inconvenience) subject to meeting the energy requirements of a predefined set of journeys.…”
Section: Contributionmentioning
confidence: 99%
See 3 more Smart Citations
“…The study found that this was especially true for EVs with larger batteries: those with capacities above 35 kWh chose to charge on average every 3.2 days, versus every 1.5 days for those with capacities under 25 kWh [51]. To address this important point, the work presented in this paper models drivers' likely charging schedules derived from week-long travel diaries, using a heuristic method originally presented in [52], in which the focus is to minimise the number of charging events (and the associated inconvenience) subject to meeting the energy requirements of a predefined set of journeys.…”
Section: Contributionmentioning
confidence: 99%
“…In this paper, a fleet of EVs is simulated within an electrical distribution network according to the spatial distribution of existing vehicles according to Census data. Each vehicle is assigned a week-long travel diary from the UK National Travel Survey (NTS) based on key demographic attributes of the driver found from Census data, and these travel diaries are used to derive charging schedules from the heuristic presented in [52] as already mentioned. By modelling the heterogeneity in travel habits amongst a population and the resulting demand from EV charging, it is suggested that this approach can contribute to a better understanding of the area and network-specific impacts of the electrification of private transport.…”
Section: Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Political guidelines in various countries to decarbonize individual mobility led to an exponential growth of Electric Vehicles (EVs) in offers and sales. However, one obstacle for the success of EVs is the so-called range anxiety [1]. Customers are afraid that an EV is not able to provide the range they need for all of their journeys.…”
Section: Introductionmentioning
confidence: 99%